PERKEMBANGAN SERANGAN TERHADAP WINDOWS DEFENDER UNTUK MENGAMBIL PENGOPERASIAN SISTEM TERINTEGRASI DENGAN HID BADUSB - Napitupulu, Willy; Salman, Muhammad (Jurnal Abdi Insani, 2024)
The Windows operating system is an operating system that is commonly used by many people. Universal Serial Bus (USB) is a mechanism used by many people with practical plug and play functionality, making data transfer fast and easy compared to other hardware. In its use, Windows has a weakness, namely that it is easy for users to experience exploitation of computers/laptops. There is a method called that makes it possible for someone to plant a reverse shell backdoor and exploit files just by connecting a USB to the target computer without being noticed. This research aims to implement and analyze the impact of attacks carried out by BadUSB . Research was carried out to see whether planting a reverse shell backdoor and exploiting files on the target computer using BadUSB could be done or not. The results obtained were that the backdoor reverse shell test using which was carried out on the Windows operating system was successfully carried out. Keywords: BadUSB, reverse shell, Linux, Programming, Python, Computer, Operation System, , HID usb.